2017
DOI: 10.1245/s10434-016-5753-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Satisfaction and Body Image After Contralateral Prophylactic Mastectomy

Abstract: Background Contralateral prophylactic mastectomy (CPM) rates have been increasing in the U.S. Though some studies have reported high overall satisfaction among women who undergo CPM, it is unclear how long-term satisfaction differs from that of women who undergo unilateral mastectomy (UM). Furthermore, few studies have assessed whether the effects of CPM on body image differ from those of breast conserving surgery (BCS) or UM. Methods We analyzed responses from a survey of women with both a personal and fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 35 publications
1
39
1
4
Order By: Relevance
“…Several themes that emerged in this study reflected this complexity, particularly the tension between some of the emotions which were commonly expressed by women regarding their treatment. Consistent with other studies that have examined satisfaction with surgical decisions, most women in our study voiced confidence and satisfaction with their surgical choice. However, despite this confidence, some women said that, at times, they felt uncertain in some way about their decision.…”
Section: Discussionsupporting
confidence: 89%
“…Several themes that emerged in this study reflected this complexity, particularly the tension between some of the emotions which were commonly expressed by women regarding their treatment. Consistent with other studies that have examined satisfaction with surgical decisions, most women in our study voiced confidence and satisfaction with their surgical choice. However, despite this confidence, some women said that, at times, they felt uncertain in some way about their decision.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, BLM has greater morbidity than unilateral mastectomy (ULM) or breast-conserving surgery with radiotherapy (breast conserving therapy [BCT]), in terms of complications, body image, recovery time, and impact on employment. [4][5][6][7][8] The choice to undergo BLM is complex. Although the probability of developing a contralateral second breast cancer has declined in the United States over time, 9 potentially due to the more widespread use of adjuvant endocrine therapy, 10 the majority of patients report that fear of a subsequent breast cancer was their primary motivation for choosing to undergo BLM.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 81 abstracts met eligibility criteria; 81 full‐text articles were reviewed, 63 were subsequently found to be ineligible, and one article was added following review of reference lists of eligible studies. A total of 19 studies were eligible for inclusion in the analysis 7,14‐32 …”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported satisfaction with reconstruction and cosmesis 15,16,30,31 (Table 3). In two studies, satisfaction was high 15,31 .…”
Section: Resultsmentioning
confidence: 99%